Sex difference in coronavirus disease (COVID-19): a systematic review and meta-analysis - Ayelign Mengesha Kassie; Biruk Beletew Abate; Mesfin Wudu Kassaw; Teshome Gebremeskel Aragie; Setamlak Adane Masresha (BMJ Open)
Objective To assess the sex difference in the prevalence of COVID-19 confirmed cases.Design Systematic review and meta-analysis.Setting PubMed, Cochrane Library and Google Scholar were searched for related information. The authors developed a data extraction form on an Excel sheet and the following data from eligible studies were extracted: author, country, sample size, number of female patients and number of male patients. Using STATA V.14 for analysis, the authors pooled the overall prevalence of men and/or women using a random-effect meta-analysis model. The authors examined the heterogeneity in effect size using Q statistics and I2 statistics. Subgroup and sensitivity analyses were performed. Publication bias was also checked.Participants Studies on COVID-19 confirmed cases were included.Intervention Sex (male/female) of COVID-19 confirmed cases was considered.Primary and secondary outcome measures The primary outcome was prevalence of COVID-19 among men and women.Results A total of 57 studies with 221 195 participants were used in the analysis. The pooled prevalence of COVID-19 among men was found to be 55.00 (51.43–56.58, I2=99.5%, p<0.001). Sensitivity analysis showed the findings were not dependent on a single study. Moreover, a funnel plot showed symmetrical distribution. Egger’s regression test p value was not significant, which indicates absence of publication bias in both outcomes.Conclusions The prevalence of symptomatic COVID-19 was found to be higher in men than in women. The high prevalence of smoking and alcohol consumption contributed to the high prevalence of COVID-19 among men. Additional studies on the discrepancies in severity and mortality rate due to COVID-19 among men and women and the associated factors are recommended.